Pelatihan Membaca dan Memahami Pantun Jenaka Tenas Effendy Di SMAN 5 Pekanbaru: Training in Reading and Understanding Tenas Effendy's Humorous Pantun at SMAN 5 Pekanbaru - Amanan; Hermansyah; Juswandi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2025)
Pantun is one of the forms of Malay oral literature that remains alive and is still used by the community. In addition to serving as entertainment and a medium of expression, pantun also functions as a tool for conveying religious and moral teachings, commonly referred to as pantun berisi (meaningful pantun), pantun tunjuk ajar (didactic pantun), or pantun nasihat (advisory pantun). Its interpretation is not only literal but also symbolic, as it is rich in meaning. Consequently, pantun can be delivered in various forms of expression, allowing the messages it carries to be disseminated more broadly and reach diverse segments of society. Therefore, the elders say, “In Malay pantun, there is wisdom.” This community service activity is aimed at the students of SMA Negeri 5 Marpoyan Damai, in line with the Riau Provincial Government's efforts to preserve and promote Riau Malay Culture. The goal is to improve students’ ability to read and understand pantun jenaka (humorous pantun) composed by Tenas Effendy. Through the involvement of the team from the Faculty of Cultural Sciences, Universitas Lancang Kuning, this activity is expected to strengthen students’ understanding of Malay culture as a whole.